(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the pedagogical foundations for forming mathematical imagination through game technologies in preschool education. It explains theoretical bases (sociocultural mediation, developmental readiness, learning trajectories), identifies key pedagogical principles (playful challenge, concreteness-to-abstraction, rule awareness, language support, collaboration, and reflection), and proposes practical strategies for designing game-based mathematical experiences. Examples show how teachers can use games to cultivate spatial visualization, pattern sense, early modeling, and flexible thinking while maintaining developmental appropriateness.